5th International Conference on Quality Innovation and Sustainability (ICQIS 2024): theory and applications (abstract book) - Morgado, Teresa (2024)
The conference themes, which address novel and advanced topics on Sustainability, Quality, and Innovation, focused on eight Special Sessions, namely, "Circular Economy and Waste Management – New Approaches, Innovative Technologies, and Business Models", "Failure Prevents: Reliability, Proactivity and Practice, "Lean, TRIZ methodologies Applied to Sustainability Management", "Modelling and Simulation: A way to promote system resilience and sustainability management", "Quality 4.0 and innovations in the digital era", "Recent Advances in Manufacturing", "Sustainability energy" and "Lean Sustainability". The conference also included the workshop "Brick by Brick: Exploring the Future of Quality Management through Serious Gaming" and an Open Forum on "Quality, Innovation and Sustainability Challenges and Opportunities" where an expert panel of many years of collective and active researchers and managers addressed the issue of balancing the activities of businesses, management, and engineering within the enterprises and institutions. The ICQIS2024 organizers believe that the meeting offered our delegates a forum for discussion and dissemination of their recent work in assessing the Sustainability, Quality, and Innovation of engineering and business services and promoting the exchange of ideas and international cooperation among scientists, managers, and engineers in this vital field of engineering and business.